Emerging Biofabrication Strategies for Engineering Complex Tissue Constructs. Issue 19 (3rd April 2017) - Pedde, R. Daniel; Mirani, Bahram; Navaei, Ali; Styan, Tara; Wong, Sarah; Mehrali, Mehdi; Thakur, Ashish; Mohtaram, Nima Khadem; Bayati, Armin; Dolatshahi‐Pirouz, Alireza; Nikkhah, Mehdi; Willerth, Stephanie M.; et al.
Abstract : The demand for organ transplantation and repair, coupled with a shortage of available donors, poses an urgent clinical need for the development of innovative treatment strategies for long‐term repair and regeneration of injured or diseased tissues and organs. Bioengineering organs, by growing patient‐derived cells in biomaterial scaffolds in the presence of pertinent physicochemical signals, provides a promising solution to meet this demand. However, recapitulating the structural and cytoarchitectural complexities of native tissues in vitro remains a significant challenge to be addressed. Through tremendous efforts over the past decade, several innovative biofabrication strategies have been developed to overcome these challenges. This review highlights recent work on emerging three‐dimensional bioprinting and textile techniques, compares the advantages and shortcomings of these approaches, outlines the use of common biomaterials and advanced hybrid scaffolds, and describes several design considerations including the structural, physical, biological, and economical parameters that are crucial for the fabrication of functional, complex, engineered tissues. Finally, the applications of these biofabrication strategies in neural, skin, connective, and muscle tissue engineering are explored. Abstract : Recent advancements in 3D bioprinting and biotextile technologies are outlined, as two emerging biofabrication approaches, developed to address the clinical need for artificial tissues and organs by facilitating the fabrication of complex, biomimetic substitutes. The specifications and capabilities of these methods, along with their applications in nervous, skin, connective and muscle tissue engineering, are explored.